Implication of Comprehensive Income Disclosure for Future Earnings and Analysts' Forecasts - CHOI, Jong-Hag (Institutional Knowledge at Singapore Management University, 2006)
This paper examines the association of comprehensive income with subsequent period net income as well as analysts’ earnings forecasts. Our results support the notion that comprehensive income is incrementally useful in predicting subsequent period changes in net income. We also document that comprehensive income is associated with analysts’ earnings forecast revisions and forecast errors. The evidence is consistent with analysts’ failure to fully utilize the information disclosed in comprehensive income. The result suggests that analysts revise their year t+1’s forecast downward when comprehensive income is smaller than net income but they do not revise the forecast upward when comprehensive income is greater than net income. This evidence on the asymmetric use of comprehensive income is consistent with the notion that the future recognition of unrecognized losses is more predictable than the future recognition of unrecognized gains.